Human Biomonitoring: from group to personalized exposure assessment in occupational settings - Duca, Radu-Corneliu (2020)
The necessity of using human biomonitoring (HBM) for chemical health risk assessment for both general population and workers has recently been brought to the fore. HBM4EU (www.hbm4eu.eu) has the main aim to coordinate and advance HBM in Europe. One of the many intended outcomes of this project is to harmonize HBM protocols and to demonstrate the utility of HBM when assessing workers exposure to chemicals. In occupational settings, analysis of environmental matrices may be insufficient to demonstrate the amount of compounds absorbed into the body. Analysis of biomarkers in biological samples to determine the internal dose is therefore an important asset in defining prevention strategies. Nevertheless, the interpretation of the HBM results might be challenging, especially at individual level, since, the absorbed dose is determined by many factors, e.g. chemical concentration, its physicochemical properties, exposure duration as well as individual factors including up-take, metabolism etc. The specificity and sensitivity of the chosen biomarker depends e.g. on its physiological half-live in the selected biological matrix. The number of compounds having recommended Biological Limit Values (BLVs) to assist in the identification of health hazards is limited. In addition, no BLVs are available for biological matrices other than urine and blood that might be related to a longer physiological half-live of the target compounds (e.g. hair) or directly related to the target organs (e.g. Exhaled Breath Condansate). However, more research is required to develop guidelines in order to choose the most appropriate biomarker and/or matrix. Within the HBM4EU occupational studies, we intend to demonstrate that the individual analysis of biomonitoring is a useful tool for personal exposure evaluation, providing information not given by inhalation and dermal exposure assessment. HBM will highlight personal working conditions and practices, taking into account individual differences and allowing more individualized measures to prevent exposure by changing individual behavior.